Experimental study of a wet mix shotcrete for primary tunnel linings—Part I: Evolution of strength, stiffness and ductility. (15th May 2022) - Smaniotto, S.; Neuner, M.; Dummer, A.; Cordes, T.; Hofstetter, G.
Abstract: A comprehensive experimental program on the mechanical, hygral and thermal behavior of a modern wet mix shotcrete is presented. The present part I deals with the evolution of the uniaxial compressive strength, splitting tensile strength, Young's modulus, and specific mode I fracture energy. The results are compared to empirical relations used in some shotcrete models. Part II deals with creep and shrinkage of shotcrete as well as with the thermal and hygral material behavior. Together, part I and part II of this study lay the foundation for the thorough calibration and validation of material models for a wet mix shotcrete. Highlights: Evolution of strength and stiffness up to the shotcrete age of 365 days. Relation between uniaxial compressive strength and splitting tensile strength. Relation between uniaxial compressive strength and Young's modulus. Evolution of specific mode I fracture energy up to the shotcrete age of 28 days. Obtained experimental results are compared with models from the literature.